POSISI MATA PELAJARAN IPA DAN IPS DALAM KURIKULUM MERDEKA DI SEKOLAH DASAR - anisah, ani siti; Widiyastuti, Ratna; Mubarokah, Gina; Istiqomah, Isti (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
This study aims to describe the position of science and social studies subjects in the independent curriculum. The research method used is a descriptive qualitative approach carried out at SDN 04 Sukanegla Garut Kota District, Garut Regency from December 2022 to January 2023. The data collection process is carried out through observations, and interviews, and processed through triangulation techniques, data collection, data reduction, and data verification. The results explained that the position of Natural Sciences and Social Sciences was united with the aim of triggering children to manage the natural and social environment in one unit, considering that elementary school-age children are in the concrete operation phase so stimulus must be given to develop their cognitive abilities. IPAS subjects in class III-V are 180 hours per year with a time allocation for projects of 36 hours per year, and class VI has 160 hours per year with a time allocation for a project of 32 hours. The position of IPAS subjects at the elementary school level on one side has a positive impact because it eases the performance of teachers and students in mapping and understanding or learning IPAS subject matter that is stored in odd semesters and even semesters. IPAS is united to be understood comprehensively and can be realized as usual, there is no reduction in material and does not reduce the essence of both subjects.